Love beyond time: Exploring the link between love spells from The Greek Magical Papyri and the 19th-century Pomeranian folktales and proverbs (Przegląd Religioznawczy – The Religious Studies Review, 2024)
Love can be considered from various scientific perspectives; regarding historical experiences, it is much easier to do so from the perspective of material history. As for the study of spiritual manifestations, many important materials are provided by preserved beliefs, practices, and magical rituals. In the following article, the author decided to compare material concerning The Greek Magical Papyri found in Egypt, which have a much more syncretic character than just Egyptian or Greek, with material concerning 19th-century spells, love procedures, and folk wisdom from Christian Pomerania. This comparison, which at first glance seems difficult to carry out, within the framework of meticulously conducted analysis, leads step by step to many significant insights regarding both love magic and the issue of love itself.